2023
DOI: 10.1093/europace/euad114
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid atrial fibrillation ablation: long-term outcomes from a single-centre 10-year experience

Abstract: Aims Hybrid atrial fibrillation (AF) ablation is a promising approach in non-paroxysmal AF. The aim of this study is to assess the long-term outcomes of hybrid ablation in a large cohort of patients after both an initial and as a redo procedure. Methods and results All consecutive patients undergoing hybrid AF ablation at UZ Brussel from 2010 to 2020 were retrospectively evaluated. Hybrid AF ablation was performed in a one-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In a recent meta-analysis Eranki et al showed freedom from AF of 78.2% and 73.6% at 1 and 3 years after CP respectively (16). In the latest study Pannone et al reported ATs free survival without AADs in non-paroxysmal AF 76.7% at 12 months, 67.5% at 24 months, 60.5% at 36 months, 53.6% at 48 months, and 46.1% at 60 months (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis Eranki et al showed freedom from AF of 78.2% and 73.6% at 1 and 3 years after CP respectively (16). In the latest study Pannone et al reported ATs free survival without AADs in non-paroxysmal AF 76.7% at 12 months, 67.5% at 24 months, 60.5% at 36 months, 53.6% at 48 months, and 46.1% at 60 months (17).…”
Section: Discussionmentioning
confidence: 99%
“…In this case endocardial mapping and ablation at first hybrid procedure is of utmost clinical importance. 18 …”
Section: Discussionmentioning
confidence: 99%